2022
DOI: 10.3389/fbioe.2022.879024
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Epithelial Polarity in Pluripotent Stem Cell-Derived Intestinal Organoids

Abstract: The inner surface of the intestine is a dynamic system, composed of a single layer of polarized epithelial cells. The development of intestinal organoids was a major breakthrough since they robustly recapitulate intestinal architecture, regional specification and cell composition in vitro. However, the cyst-like organization hinders direct access to the apical side of the epithelium, thus limiting their use in functional assays. For the first time, we show an intestinal organoid model from pluripotent stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…In fact, both formulations result in the accumulation of ECM proteins at the surface of the organoids, leading to polarity establishment and rosette formation within 3 days. This is in contrast with other organoid systems in which both exECM presence and jellification are needed to establish apical-basal polarity ( Inman & Bissell , 2010; Kakni et al ., 2022; Plachot et al ., 2009). Furthermore, early morphological rearrangements are maintained in exECM +L organoids after Matrigel is removed from the culture medium, indicating that continuity of exposure is also unnecessary.…”
Section: Discussionmentioning
confidence: 73%
“…In fact, both formulations result in the accumulation of ECM proteins at the surface of the organoids, leading to polarity establishment and rosette formation within 3 days. This is in contrast with other organoid systems in which both exECM presence and jellification are needed to establish apical-basal polarity ( Inman & Bissell , 2010; Kakni et al ., 2022; Plachot et al ., 2009). Furthermore, early morphological rearrangements are maintained in exECM +L organoids after Matrigel is removed from the culture medium, indicating that continuity of exposure is also unnecessary.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, human intestinal organoid models with reversed polarity have been described in order to facilitate the access to the apical surface of the organoids. 28 , 29 Based on our existing reversed polarity intestinal organoid model, 29 here, we developed apical-out intestinal organoids in hypoxic conditions (5% O 2 ), aiming to create a more physiologically relevant in vitro model for host-microbiome and host-pathogen interaction studies. Briefly, human embryonic stem cells (H9 cells) were aggregated to create homogeneous EBs using polymer film-based microwell arrays ( Figure 1(a) , Supplemental Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that pluripotent stem cell-derived organoids recapitulate closely the cellular composition of the in vivo intestine. 29 , 40 To assess the differentiation capacity and maturation level of apical-out organoids in hypoxic conditions, we performed gene expression analysis for both proliferation and differentiation of intestinal cell lineages after 30 days in culture and compared them with apical-in organoids grown embedded in Matrigel domes and with apical-out organoids grown in normoxic conditions (21% O 2 ) ( Figure 1(b) ). Specifically, we evaluated the expression of the leucine-rich repeat-containing G-protein-coupled receptor 5 ( LGR5 ), the sex determining region Y-box 9 ( SOX9 ), the Krueppel-like factor 5 ( KLF5 ) and the Achaete scute-like 2 ( ASCL2 ), all indicators of proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations